Accuracy Of Pediatric Risk Of Mortality (PRISM III) Score In Predicting Mortality Risk Among Children Admitted In Pediatric Intensive Care Unit - Huma Muzzammil; Muhammad Rafique; Yousuf Yahya; Waseem Jamalvi; Seema Aftab; Noor- (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
Objective: To assess the accuracy of pediatric risk of mortality score in predicting mortality risk among children admitted in the pediatric intensive care unit. Methods: It is a descriptive cohort study conducted at PICU. It was conducted over six months from December 2022 to June 2022. All patients admitted in PICU with critical illness having age 1 month to 12 years of either gender was consecutively enrolled. Patients were classified in 3 groups accord ing to the PRISM scores 1-10 (low risk), 11-20 (moderate risk), and 21-30 (high risk) was also done. The accuracy of PRISM III score was defined based on the presence of moderate or high risk of mortality at the time of hospitalization in the PICU among patients who died within 14 days. Data was analyzed on SPSS version 24. Results: Of 135 patients, the mean age of the patients was 2.65 ±2.14 years. There were 90 (66.6%) with d"3 years of age while 45 (33.3%) with >3 years of age. Low PRISM risk score was observed in 65 (48.1%), moderate in 64 (47.4%), and high in 6 (4%) patients. Mortality was observed in 28 (20.7%) patients. The sensitivity of the PRISM score is found to be 94.8%, the specificity is 62.8%, and positive predictive value of 33.9%, negative predictive value was 95.9%. The accuracy of the PRISM score is found to be 65.57%. Conclusion: PRISM III is a reliable score in predicting mortality risk among children admitted to the Pediatric intensive care unit.